Kiwifruit effect on adipose tissue cell size and cholesteryl ester transfer protein gene expression in high-fat diet fed Golden Syrian hamsters - Zahra Zaherijamil; Narjes Rezaei; Mohammad Hashemnia; Shirin Moradkhani; Massoud Saidijam; Iraj Khodadadi; Ebrahim Abbasi Oshaghi; Heidar Tavilani (Mashhad University of Medical Sciences, 2019)
Objective: The effects of kiwifruit on the histology and cell size of adipose tissue in hyperlipidemic models have not yet been reported. Therefore, this study aimed to investigate the effect of kiwifruit on the adipose tissue cell size and activity as well as the gene expression of cholesteryl ester transfer protein (CETP) in high-fat diet (HFD) fed hamsters. Materials and Methods: Forty-two male Syrian hamsters were divided into six groups. Control normal (CN) hamsters received normal diet, control HFD (CHF) were fed with a HFD plus a normal diet (15% butter fat + 0.05% cholesterol + a normal diet). Two groups were fed with normal diet including kiwifruit (1.86; Nd.1 or 3.73 g/kg; Nd.2) and two groups were fed with HFD including kiwifruit (1.86;HFd.1or 3.73 g/kg; HFd.2), for 8 weeks. Results: Histological examination of adipose tissue showed that the cell size was significantly reduced in the kiwifruit-treated groups (low and high dose) in comparison to their control groups (p<0.05). Kiwifruit supplementation (low and high dose) in normal and HFD groups significantly increased gene expression of CETP in adipose tissue. Kiwifruit had no significant effect on serum concentration of low-density lipoprotein cholesterol, total cholesterol and triglyceride. Although, high-density lipoprotein cholesterol concentration increased in HFD-fed hamsters supplemented with 3.73 g/kg of kiwifruit (p<0.05). Conclusion: Kiwifruit consumption reduces the size of adipocytes and increases the expression of CETPgene in adipose tissue cells. Despite the increases in CETP expression in adipose tissue, its activity in serum was not changed following kiwifruit supplementation.